Effects of stress on bone health in children - Sohail, Zaineb; Hadi, Norhayati binti Abd; Lam, Edna Hiu Tung; Asghar, Muhammad; Zaman, Farasat (Frontiers in Endocrinology, 2026)
Chronic psychological stress is increasingly recognized as a major public health concern, contributing to cardiovascular disease, obesity, asthma, and impaired bone health. Although the mechanisms linking stress to skeletal dysregulation are well characterized in adults, pediatric studies remain limited. Longitudinal and mechanistic studies are needed to clarify how stress affects bone accrual during childhood. Both preclinical and clinical data show that stress can influence bone health through endocrine and immune pathways as well as via altered dietary intake, high or reduced physical activity, medications and disrupted sleep patterns. Elevated stress may also increase oxidative stress, which in turn generates mitochondrial reactive oxygen species (ROS), impairing stem cells differentiation potential, osteoblast and chondrocyte function and suppressing bone formation and growth. In addition, conditions marked by high levels of the pro-inflammatory cytokines TNF-α and IL-6, as well as by elevated exogenous or endogenous glucocorticoids (GCs), further increase cellular oxidative stress. Interventions targeting oxidative stress, such as growth hormone, vitamins C and E, or bisphosphonates, may mitigate skeletal deficits. Here, we review clinical and preclinical evidence on the direct and indirect effects of psychological stress on pediatric bone health.